2009
DOI: 10.1158/1078-0432.ccr-08-1535
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Efficacy of a DR5-Specific TRAIL Variant over Recombinant Human TRAIL in a Bioluminescent Ovarian Cancer Xenograft Model

Abstract: Purpose: Recombinant human tumor necrosis factor-related apoptosis-inducing ligand (rhTRAIL) is clinically evaluated as novel anticancer drug. rhTRAIL-DR5, a rhTRAIL variant that specifically binds to DR5 receptor, has recently been developed. We investigated whether rhTRAIL-DR5 is more efficient than rhTRAIL in combination with cisplatin in DR5-expressing human A2780 ovarian cancer cells. Design: Effect of cisplatin alone or in combination with rhTRAIL or rhTRAIL-DR5 on DR5 surface expression, apoptosis, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
2
40
1
Order By: Relevance
“…1B and 2C). It has been recently shown that a modified TRAIL ligand that specifically binds to DR5 has a more pronounced apoptotic effect dependent on cisplatin-induced DR5 expression than TRAIL in vitro as well as in an orthotopic bioluminescent ovarian cancer mouse model (41). Collectively, the described data support the importance of drug-induced DR5 upregulation in the enhanced sensitivity of ovarian cancer cells to TRAIL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…1B and 2C). It has been recently shown that a modified TRAIL ligand that specifically binds to DR5 has a more pronounced apoptotic effect dependent on cisplatin-induced DR5 expression than TRAIL in vitro as well as in an orthotopic bioluminescent ovarian cancer mouse model (41). Collectively, the described data support the importance of drug-induced DR5 upregulation in the enhanced sensitivity of ovarian cancer cells to TRAIL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…A positive cooperation between cisplatin and TRAIL ligands/agonists has been reported in different preclinical models of colon carcinoma, esophageal squamous cell carcinoma, ovarian cancer, and NSCLC (Duiker et al, 2009;Frese et al, 2009;Kondo et al, 2006;Lacour et al, 2003;Reddy et al, 2004). TRAIL agonists have achieved the clinical setting (Pennarun et al, 2010).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Development of the luciferase-transfected subline A2780 luc1 was described by Duiker et al (17). The SK-BR-3 (HER2-overexpressing) breast cancer and KATO-III (HER2-overexpressing) gastric cancer cell lines were obtained from American Type Culture Collection.…”
Section: Cell Linesmentioning
confidence: 99%